PAR1‐stimulated platelet releasate promotes angiogenic activities of endothelial progenitor cells more potently than PAR4‐stimulated platelet releasate. (31st January 2015) - Huang, Z.; Miao, X.; Luan, Y.; Zhu, L.; Kong, F.; Lu, Q.; Pernow, J.; Nilsson, G.; Li, N.
Summary Background Endothelial progenitor cells (EPCs) are important for endothelial regeneration and angiogenesis. Thrombin protease‐activated receptor 1 (PAR1) PAR1 and PAR4 stimulation induces selective release of platelet proangiogenic and antiangiogenic regulators. Objective To investigate if PAR1‐stimulated platelet releasate (PAR1‐PR) and PAR4‐PR regulate angiogenic properties of EPCs in different manners. Methods and Results EPCs were generated from peripheral mononuclear cell culture. Washed platelets (2 × 109 mL–1) were stimulated by PAR1‐activating peptide (PAR1‐AP; 10 μmol L–1) or PAR4‐AP (100 μmol L–1) to prepare PAR1‐PR and PAR4‐PR, respectively. PAR1‐PR or PAR4‐PR had little influence on EPC proliferation. EPC migration experiments using a modified Boyden chamber showed that both platelet releasates facilitated EPC migration. As for in vitro tube formation on Matrigel, PAR1‐PR and PAR4‐PR similarly enhanced capillary‐like network formation of EPCs in the complete EPC medium containing 10% FBS and a cocktail of growth factors, while PAR1‐PR more profoundly increased EPC tube formation in basal culture medium supplemented with only 0.5% FBS than did PAR4‐PR. The latter was confirmed in the murine angiogenesis model of subcutaneous Matrigel implantation. Moreover, blockade of vascular endothelial growth factor, stromal cell–derived factor 1α, or matrix metalloproteinases attenuated EPC migration and tube formation, suggesting a cooperation of these factors in the enhancements. Conclusions PAR1‐PR enhances vasculogenesis more potently than PAR4‐PR, and the enhancements require a cooperation of multiple platelet‐derived angiogenic regulators.